2007
DOI: 10.1002/hed.20671
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for complications in elderly patients who underwent head and neck oncologic surgery

Abstract: It is possible to predict postoperative complications in older patients with head and neck tumors who underwent oncologic surgery using clinical preoperative variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 29 publications
5
51
0
6
Order By: Relevance
“…In other studies [18,[25][26][27][28] mean time of restoration a normal feeding was 25 days and in Pellini's study was in less than 1 month for 61.5 % of patients [22]. The time of removal of the feeding tube ranged in literature from 10-96 days [28] to 12-90 days [18], in our study was 4-230 days.…”
Section: Complications and Functional Resultssupporting
confidence: 38%
“…In other studies [18,[25][26][27][28] mean time of restoration a normal feeding was 25 days and in Pellini's study was in less than 1 month for 61.5 % of patients [22]. The time of removal of the feeding tube ranged in literature from 10-96 days [28] to 12-90 days [18], in our study was 4-230 days.…”
Section: Complications and Functional Resultssupporting
confidence: 38%
“…Several recent studies have shown that the benefits of definitive treatment strategies extend to even the oldest oncology patients. Much of the prior research has focused upon the implications for older women with breast cancer [21][22][23], but also across a variety of different cancer diagnoses [24][25][26]. This improvement in outcomes, including survival rates, social and role functioning, and overall quality of life, is observed even among individuals with numerous other medical comorbidities [27].…”
Section: Discussionmentioning
confidence: 98%
“…partial resection, total thyroidectomy or therapeutic lymphadenectomy) the better the results in terms of survival [1,16,17]. On the one hand, it is unquestionable that the risk from surgery in geriatric patients is greater than in non-geriatric patients in virtue of the fact that there are more frequent co-morbidities with a subsequent increase in complications of a general nature [18,19]. On the other hand, several studies have demonstrated that the number of complications specifically linked to thyroid surgery in geriatric patients is essentially superimposable on those of younger patients [11e13,20]: in consideration of the nature of the pathologies examined, this may justify more aggressive surgical approaches or at the very least not more restricted compared to those set down for younger patients.…”
Section: Discussionmentioning
confidence: 99%